SCREEN WRITING CONFERENCE, BRUSSELS, SEPTEMBER2011, CONFERENCE REPORT. (29th August 2012) - Pallant, Chris
'Beyond Boundaries: Screenwriting Across Media', The Fourth Research Network Conference, Université Libre de Bruxelles, Brussels, 8–10 September 2011